Tafsir Kontemporer: Metodologi, Paradigma dan Standar Validitasnya - Eni Zulaiha (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
Feminist exegesis (tafsir) is a unique genre emerges in contemporary era when gender issue become a global concern. The paradigm of this tafsir started from the asumpsion that the Qur’anic principle of male-female relationship should be based on justice (al-‘adalah), equality (al-musawah), appropriateness (al-ma’ruf), and conssensus (syura). Thus, any exegesis produced in classical period which violate all those principles are considered unacceptable, especially in relation to the current situation which differ from that of previous time. Feminist tafsir employs gender analisys as a tool to differentiate between God given condition that is unchangeable to gender as social construction that is changeable. In addition, hermeneutics is considered an appropriate approach chosen in feminist tafsir along with thematic method to interprete verses about gender relation in the Qur’an. With this methodology, its aim is to produce tafsir with more intersubjective and critical insight related to gender relation.